Does Defensive Medicine Change the Behaviors of Vascular Surgeons? A Qualitative Review. (1st October 2015) - Frati, Paola; Busardò, Francesco Paolo; Sirignano, Pasqualino; Gulino, Matteo; Zaami, Simona; Fineschi, Vittorio
Abstract : Although in literature few successful claims have been shown in comparison with other medical specialties such as gynaecology and orthopaedics, vascular surgery is included among high-risk specialties. The high-risk of receiving medical claims may lead vascular surgeons to practice defensive medicine, as is normal in several other areas of clinical practice. No studies are available to our knowledge of the incidence of defensive medicine in the field of vascular surgery. Taking into consideration the scarce amount of information, the authors provide a critical discussion regarding the application of defensive medicine behaviour among vascular surgeons.